Identification of compounds active against quiescent artemisinin-resistant Plasmodium falciparum parasites via the quiescent-stage survival assay (QSA). (12th July 2020) - Reyser, Thibaud; Paloque, Lucie; Ouji, Manel; Nguyen, Michel; Ménard, Sandie; Witkowski, Benoit; Augereau, Jean-Michel; Benoit-Vical, Françoise
Abstract: Background: Quiescence is an unconventional mechanism of Plasmodium survival, mediating artemisinin resistance. This phenomenon increases the risk of clinical failures following artemisinin-based combination therapies (ACTs) by slowing parasite clearance and allowing the selection of parasites resistant to partner drugs. Objectives: To thwart this multiresistance, the quiescent state of artemisinin-resistant parasites must be taken into consideration from the very early stages of the drug discovery process. Methods: We designed a novel phenotypic assay we have named the quiescent-stage survival assay (QSA) to assess the antiplasmodial activity of drugs on quiescent parasites. This assay was first validated on quiescent forms from different artemisinin-resistant parasite lines (laboratory strain and field isolates), using two reference drugs with different mechanisms of action: chloroquine and atovaquone. Furthermore, the efficacies of different partner drugs of artemisinins used in ACTs were investigated against both laboratory strains and field isolates from Cambodia. Results: Our results highlight that because of the mechanism of quiescence and the respective pharmacological targets of drugs, drug efficacies on artemisinin-resistant parasites may be different between quiescent parasites and their proliferating forms. Conclusions: These data confirm the high relevance of adding the chemosensitivity evaluation of quiescent parasites by the specific in vitro QSA to the antiplasmodial drug development process in the current worrisome context of artemisinin resistance.